Riba According to Sjafrudin Prawiranegara (1911 – 1989) and Muhammad Syafii Antonio (1967) (Critical Comparative Analysis of Islamic Legal Theory Perspective)
Sjafrudin Prawiranegara and Syafii Antonio are two influential figures of Islamic economists in Indonesia. Both are considered to represent two different poles of Islamic economics. Sjafrudin represented critical thinking, while Syafii Antonio represented mainstream thinking. This paper was made with a theory approach istinbat